2022
DOI: 10.5414/alx02327e
|View full text |Cite
|
Sign up to set email alerts
|

The role of LPS and CpG in the farm effect against allergies, and beyond

Abstract: The prevalence of allergic disease has increased significantly over the past decades. Although allergies are inherently multifactorial and heterogenous; environmental, maternal, and early-life microbial exposures could strongly modify disease risk. The effects of environmental microbiota are illustrated by the “farm effect”, showing protection against asthma when children grow up on traditional farms. Recent studies have further revealed an important role for early-life exposure to a microbe-rich environment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Both entry routes of endotoxin have been described to contribute to the prevention of atopy [15,25,60]. However, it is important to highlight that the timedependent effects of endotoxin or farm exposure are strongest in two critical windows: prenatal and early childhood [61]. In most studies, this early childhood window refers to the first 3 weeks in mice and the first year of life in humans [61,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both entry routes of endotoxin have been described to contribute to the prevention of atopy [15,25,60]. However, it is important to highlight that the timedependent effects of endotoxin or farm exposure are strongest in two critical windows: prenatal and early childhood [61]. In most studies, this early childhood window refers to the first 3 weeks in mice and the first year of life in humans [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to highlight that the timedependent effects of endotoxin or farm exposure are strongest in two critical windows: prenatal and early childhood [61]. In most studies, this early childhood window refers to the first 3 weeks in mice and the first year of life in humans [61,62]. However, some studies have shown that the protective effects of LPS exposure in mice can persist into adulthood [18,63].…”
Section: Discussionmentioning
confidence: 99%